Data on the warfare and bladed weapons on the balkans from the 7th – 11th century in artistic sources (Research Announcements "Heritage BG", 2025)
In the present study was analyzed the data related to the development of a cold weapons in the Balkans within 7th – 11th century, according to artistic monuments. Particular attention to some miniatures within manuscripts is paid. That provides direct or indirect information about the development of early medieval warfare and armaments of Byzantium and the First Bulgarian Kingdom, that arosed on ancestral Byzantium territories. In the pictorial medieval monuments from South-Eastern Europe considered in the present study, it is noteworthy that the warriors are mostly armed with spears, while with sabers and swords are mostly rulers and high-ranking military figures depict. This presupposes the existence of a certain symbolism towards this type of cold weapon and its definition as an insignia of power and prestige. However, if we go beyond information from Byzantine artistic monuments and turn our attention to narratives, we will find that swords and sabers are not just elite weapons. The lack of a large number of early medieval finds of bladed weapons in the territory of the Lower Danube is probably due to their expensive and complex manufacture, as well as the symbolism that they ‘carry’, which in turn implies a long period of use and transmission from generation to generation. References:Primary sources:Komnene 1972: Komnene, Anna. ‘Aleksiada’. Gratski izvori za balgarskata istoriya, No. 8, 7-149.Chatzelis, Harris 2017: Chatzelis Georgios, Harris Jonathan. A Tenth-Century Byzantine Military Manual: The Sylloge Tacticorum. New York.McGeer 1994: McGeer, Eric. The Praecepta militaria of the Emperor Nikephoros II Phokas (963-969). In: Sowing the Dragon’s Teeth: Byzantine Warfare in the Tenth Century. Washington, 3-78.Nicolai I papae 1960: Nicolai I papae. ‘Responsa Nicolai I papae ad consulta Bulgarorum’. – Latinski izvori za balgarskata istoriya, No. 2, 65-125.Porphyrogenitus 1964: Porphyrogenitus, Constantinus. ‘De Ceremoniis aulae Byzantinae’. – Gratski izvori za balgarskata istoriya, No. 5, 220-229.Porphyrogenitus 1964: Porphyrogenitus, Constantinus. ‘De administrando imperio’. – Gratski izvori za balgarskata istoriya, No. 5, 198-220.Zonaras 1968: Zonaras, Joannes. „Istoriya“. – Gratski izvori za balgarskata istoriya, No. 7, 149-208.Secondary sources:Barthélemy 2010: Barthélemy, Dominique. Ritsarstvoto – Ot antichna Germaniya do Frantsiya prez 12 vek. Sofia.Berger, Zhuber-Okrog 2017: Berger, Sarah, Karoline Zhuber-Okrog. Zlatnoto sakrovishte ot Nagyszentmiklós Natsionalen arheologicheski muzey: Katalozi. 6. Sofia, 77-161.Beshevliev 1979: Beshevliev, Veselin. Parvobalgarski nadpisi. Sofia.Bozhkov 1972: Bozhkov, Atanas. Miniatyuri ot Madridskiya rakopis na Yoan Skilitsa. Sofia.Georgiev 1986: Georgiev, Pavel. Nahodka ot vikingsko vreme. - Muzei i pametnitsi na kulturata, No. 3, 19-23.Georgiev 2008: Georgiev, Pavel. Kalap za monetovidni znatsi (brakteati) s psevdokuficheski nadpis ot Pliska. In: Yubileen sbornik v chest na 100-godishninata ot rozhdenieto na d-r Vasil Haralanov (1907–2007). Shumen, 353-364.Glebov, Ivanov 2007: Glebov, Vyacheslav, Aleksey Ivanov. Kochevnicheskoye pogrebeniye khazarskogo vremeni iz mogil’nika Talovyy II. In: Srednevekovyye drevnosti Dona: Materialy i issledovaniya po arkheologii Dona. 2. Moskva, Jerusalem, 154-177.Duychev 1962: Duychev, Ivan. Miniatyuri na Manasievata letopis. Sofia.Kolias 2012: Kolias, Taxiarchis. Vizantiyski orazhiya. Veliko Tarnovo.Mikov 2010: Mikov, Rumen. Romfeyata ot Kabile v konteksta na problemite, svarzani s datiraneto na orazhiyata ot tazi kategoriya. Razprostranenie i proizvodstvo. – Stephanos Archaeologicos: In honorem Professoris Stephcae Angelova. Studia Archaeologica Universitatis Serdicensis, No. 5, 207-227.Minaeva, Holmquist 2012: Minaeva, Oksana, Lena Holmquist. Balgarski paraleli na iztochnite nahodki na metaloplastikata ot Birka. Plovdiv.Minaeva 2013: Minaeva, Oksana. Vikingski nahodki na Balkanite: Funktsiya, semantika, stilova interpretatsiya. Sofia.Ovcharov 1982: Ovcharov, Dimitar. Balgarski srednovekovni risunki – grafiti. Sofia.Petrov, Gyuzelev 1978: Petrov, Petar, Vasil Gyuzelev. Hristomatiya po istoriya na Balgariya. 1. Sofia.Primov 1981: Primov, Borislav. Ukrepvane i teritorialno razshirenie na Balgarskata darzhava prez parvata polovina na 9 vek. In:  Istoriya na Balgariya, 2, Sofia, 130-160.Rabovyanov 2011: Rabovyanov, Deyan. Early Medieval sword guards from Bulgaria. – Archaeologia Bulgarica, No. 15(2), 73-86.Rabovyanov 2013: Rabovyanov, Deyan. Srednovekovni predpaziteli za mech ot Balgariya. - Prinosi kam balgarskata arheologiya, No. 7, 99-114.Werner 1988: Werner, Joachim. Pogrebalnata nahodka ot Malaya Pereshchepina i Kubrat – han na balgarite. Sofia.Yotov 2003: Yotov, Valeri. Nakraynitsi ot grupata ‘germanski chetirinog zvyar“ v „zhivotinskiya stil na Baltiysko more’. - Pliska-Preslav, No. 9, 132-135.Yotov 2004: Yotov, Valeri. Vaorazhenieto i snaryazhenieto ot balgarskoto Srednovekovie (7–11 vek). Sofia.Yotov 2014: Yotov, Valeri. Vizantiyskiyat mech (7–11 vek)Tsar Samuil (+ 1014) v bitka za Balgariya. Sofia, 91-103.Yotov 2015: Yotov, Valeri. Predpazitel na mech ot Pliska. - Pliska-Preslav, No. 11, 233-241.Zlatarski 1970: Zlatarski, Vasil. Istoriya na balgarskata darzhava prez srednite vekove. Istoriya na Parvoto balgarsko tsarstvo. Epoha na huno-balgarskoto nadmoshtie (679 – 852). 1(1). Sofia.Anker 1998: Anker, Ellen. What Life Was Like. Amid Splendor and Intrigue: Byzantine Empire AD 330-1453. Virginia.Bagautdinov, Bogačev, Zubov 1998: Bagautdinov, Riza, Aleksey Bogačev, Sergey Zubov. Prabolgary na Sredney Volge. Samara.Hoffmeyer 1966: Hoffmeyer, Ada. Military Equipment in the Byzantine Manuscript of Scylitzes in Biblioteca Nacional de Madrid. – Gladius, No. 5, 1-194.Kamburov 2021: Kamburov, Samuil. Early Medieval Weapons for Close Combat of North European Origin Found within Present-day Bulgarian Territory. – Bulgarian e-Journal of Archaeology Supplements, No. 8, 89-116.Kolias 1988: Kolias, Taxiarchis. Byzantiniche Waffen: Ein Beitrag zur byzantinischen Waffenkunde von den Anfängen bis zur lateinischen Eroberung. Wien.Oakeshott 1960: Oakeshott, Ewart. The Archaeology of Weapons: Arms and Armour from Prehistory to the Age of Chivalry. Woodbridge.Popov 2016: Popov, Stoyan. Early mediaeval sword and sword-pommels from North-Eastern Bulgaria. – Russkiy sbornik, No. 8(1), 109-112.Stanilov, Komatarova-Balinova 2018: Stanilov, Stanislav, Evgeniya Komatarova-Balinova. Ein Beinamulett aus den Ruinen der römischen Stadt Augusta. In: Sonderdruk Monographien des RGZM, Band 150. Mainz, 375-392.Sybel 1909: Sybel, Ludwig von. Christliche Antike: Einführung in die altchristliche Kunst: Plastik, Architektur und Malerei. 2. Marburg.Yotov 2003: Yotov, Valeri. The Vikings on the Balkans. Varna.Yotov 2008: Yotov, Valeri. The Vikings on the Balkans (10th–11th centuries). Strategic and tactical changes. New archaeological data on the weaponry. – Arhaeologia Baltica, No. 8, 321-327.Yotov 2011: Yotov, Valeri. Byzantine Time Swords (10th -11th Centuries) in Romania. - Studia Universitatis Cibiniensis (Series Historica), No. 8(1), 35-45.Yotov 2018: Yotov, Valeri. Data about northmen`s presence in the Lower Danube area. – Studia Romana et Mediaevalia Europaensia, No. 13, 467-484.Yotov, Valeriev, Totev 2018: Yotov, Valeri, Yoto Valeriev, Boyan Totev. Traces of Scandinavian Warriors’ Presence on the Balkans. – Acta Musei Varnaensis, No. 10(1), 103-122.Sites:Ryzhevolosyy Rustam – mificheskiy geroy Shakhname – https://caa-network.org/archives/17549Europeana – https://www.europeana.eu/en/item/22/_21525Europeana – https://www.europeana.eu/en/item/22/_21524Kellett 2013: Kellett, Rachel. Royal armories MS I.33: The judicial combat and the art of fencing in thirteenth- and fourteenth- century German literature – http://www.tandfonline.com/doi/full/10.1179/0078719112Z.0000000003
Keywords: Early Middle Ages; Byzantine Empire; First Bulgarian Kingdom; manuscripts; armament; swords; sabers